Of mice and men: the need for humanized mouse models to study human IgG activity in vivo. - Lux, Anja; Nimmerjahn, Falk (Journal of clinical immunology, 2013)
Antibodies of the IgG isotype have a variety of pro- and anti-inflammatory effector functions, making them attractive platforms for the development of novel therapeutic approaches. Animal model systems have been invaluable to the understanding of the underlying mechanisms of IgG activity. However, differences in the IgG subclasses and Fc receptors responsible for mediating IgG-dependent effector functions, even between such closely related species as humans and monkeys, make it difficult to predict the activity of human IgG in vivo. This review will focus on currently available animal model systems used to study human IgG activity and will propose novel model systems that might enable us to obtain a closer look at the molecular and cellular mechanisms underlying human IgG activity in vivo.